Equine adipose mesenchymal stem cells (eq-ASCs) appear to have higher potential for migration and musculoskeletal differentiation. (August 2019) - Shojaee, Asiyeh; Parham, Abbas; Ejeian, Fatemeh; Nasr Esfahani, Mohammad Hossein
Abstract: Equine adipose-derived mesenchymal stem cells (eq–ASCs) possess excellent regeneration potential especially for treatment of musculoskeletal disorders. Besides their common characteristics, MSCs harvested from different species reveal some species-specific and donor-dependent behaviors. Hence, the molecular analysis of MSCs may shed more light on their future clinical application of these cells. This study aimed to investigate some behavioral aspects of eq-ASCs in vitro which may influence the efficacy of stem cell therapy. For this purpose, MSCs of a donor horse were isolated, characterized and expanded under normal culture conditions. During continuous culture condition, eq-ASCs were started to formed aggregated structures that was accompanied with the up-regulation of migratory related genes including transforming growth factor beta 1 ( TGFB1) and its receptor 3 ( TGFBR3), and snail family transcriptional repressor 1 ( SNAI1 ), E - cadherin ( CDH1 ) and β-catenin ( CTNNB1 ). Moreover, the expression of a musculoskeletal progenitor marker, scleraxis bHLH transcription factor ( SCX ), was also increased after 3 days. In order to clarify the impact of TGFB signaling pathway on cultured cells, gain– and loss-of-function treatment by TGFB3 and SB431542 (TGFB inhibitor) were performed, respectively. We found that TGFB3 treatment exaggerated the aggregate formation effects, in some extend via induction of cytoskeletal actin rearrangement, while inhibition of TGFB signaling pathway by SB431542 reversed this phenomenon. Overall, our findings support the fact that eq-ASCs have an inherent capacity for migration, which was enhanced by TGFB3 treatment and, this ability may play crucial role in cell motility and wound healing of transplanted cells. Highlights: Equine adipose-derived mesenchymal stem cells (eq-ASCs) reveal an increased expression of migratory related genes. Eq-ASCs show an increased expression of SCX as a musculoskeletal progenitor marker. TGFB3 enhances the migratory behavior of eq-ASCs. SB431542 (as a TGFB inhibitor) inhibit the effects of TGFB3 on the migratory behavior of eq-ASCs.